Impact of pollution in Budha Nallah brook on the occurrence of fishes in river Satluj - Kaur, Tejinder (Indian Journal of Fisheries, 2011)
A study of Budha Nallah (BN) brook, a heavily polluted tributary of river Sutlujshowed, the occurrence of 42 fish species in the upstream (US) region (8-10 kmbefore the confluence of BN with the river) and 35 fish species in the downstream(DS) region (40-42 km following confluence of BN with the river). The confluenceof BN with the river led to the disappearance of 7 fish species like Ambassis ranga,Amblypharyngodon mola, Catla catla, Ompok bimaculatus O. pabda, Punitus tictoand Xenentodon cancila whereas 8 fish species namely Aspidoparia morar, Chelabacaila, C. laubuca, Cirrhina reba, Crossocheilus latius, Osteobrama cotio, Puntiusstigma and Trichogaster fasciatus are under the process of elimination as revealedby their low abundance in the DS region. The stretch between the point of confluenceand area of collection in downstream region did not show occurrence of fishesindicating their absence in the region